Multivariate analysis application to determine the preponderance of edaphoclimatic factors in the production of seeds from tropical prairie grasses - Febles, Gustavo; Torres, Verena; Ba?os, R.; Ruiz, Tom?s E.; Y??ez, S.; Echeverr?a, Jahel (Cuban Journal of Agricultural Science, 2011)
The trial was conducted to develop a strategy for determining the production of tropical prairie seeds with greater accuracy, through the combination of edaphoclimatic indicators and multivariate analysis of principal components and conglomerates. The data were collected from farms with seeds sown in specific regions of Cienfuegos, Villa Clara, Sancti Spiritus, Camag?ey, Granma and Guantanamo. The species were Panicum maximum, Andropogon gayanus, Brachiaria decumbens, Brachiaria brizantha, Chloris gayana, and Cenchrus ciliaris. The results showed the preponderance of the variables: total rainfall and rainfall in the rainy season; maximum, minimum and mean temperature; soil depth, rocks, phosphorus, and drainage. The method of conglomerates produced four groups: Cienfuegos; Guant?namo, Villa Clara and Camag?ey; S. Spiritus; and Granma. These variables accounted for 88.8 % of the variability in the analysis of conglomerates. The mathematical analysis showed that there was no relevance for the yield, which varied between 147.8 and 240 kg/ha. This may indicate that the species performance does not vary, in a relevant form, between regions. It was concluded that the combined method was useful to study the influence of the composite of edaphoclimatic factors, species, and regions of the country. Key words: multivariate analysis, seed production, tropical prairie species, edaphoclimatic indicators.